Capital Structure Changes in the Automotive Sector Affected By Financial Performance - Roni, May; Meriyati, Meriyati; Hermanto, Agus (El-Barka Journal of Islamic Economics and Business, 2021)
The purpose of this study was to determine the effect of financial performance to changes in capital structure. Data analysis techniques using multiple linear regression with panel data approach that uses statistical test equipment EViews 7. The results showed that the variable gross profit margins (GPM), net profit margins (NPM), and return on investment (ROI) significantly influence the debt equity ratio (DER). F test results simultaneously shows that there is no significant effect between gross profit margins (GPM), net profit margins (NPM), and return on investment (ROI) on the capital structure (debt equity ratio). The theory of capital structure that supports this research is Balancing Theory.       Tujuan penelitian ini adalah untuk mengetahui pengaruh Kinerja Keuangan terhadap perubahan Struktur Modal. Teknik analisis data menggunakan Regresi linier berganda dengan pendekatan data panel yang menggunakan alat uji statistik EViews 7. Hasil penelitian menunjukkan bahwa variabel gross profit margins (GPM), net profit margins (NPM), dan return on investment (ROI) berpengaruh signifikan terhadap debt equity ratio (DER). Hasil uji F secara simultan terdapat pengaruh yang tidak signifikan antara gross profit margins (GPM), net profit margins (NPM), dan return on investment (ROI) terhadap Struktur Modal (debt equity ratio). Teori struktur modal yang mendukung penelitian ini adalah Balancing Theory.